2022
DOI: 10.11604/pamj.2022.41.34.30815
|View full text |Cite
|
Sign up to set email alerts
|

Speciation and antifungal susceptibility of Candida isolates from diabetic foot ulcer patients in a tertiary hospital in Kenya

Abstract: Introduction diabetic foot ulcer is the leading cause of hospital admissions, lower limb amputation and death among diabetic patients. Little information is available on fungal isolation in diabetic foot ulcer patients, especially in sub-Saharan Africa. This study aimed to describe Candida species infecting diabetic foot ulcers in patients receiving clinical care at Kenyatta National Hospital and assess their antifungal susceptibility profile. Methods this was a cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
0
7
1
1
Order By: Relevance
“…Among candida species, C. auris have emerged as a pandrug resistant organism which lead to prolong hospital stay and healthcare cost. 16 In the present study we found 62 isolates of Candida species from 150 clinical specimens. About 80% of the Candida species were isolated from urine and sputum sample, which indicates the higher incidence and distribution of Candida species causing urinary tract and respiratory tract infections.…”
Section: Discussionmentioning
confidence: 57%
“…Among candida species, C. auris have emerged as a pandrug resistant organism which lead to prolong hospital stay and healthcare cost. 16 In the present study we found 62 isolates of Candida species from 150 clinical specimens. About 80% of the Candida species were isolated from urine and sputum sample, which indicates the higher incidence and distribution of Candida species causing urinary tract and respiratory tract infections.…”
Section: Discussionmentioning
confidence: 57%
“…Penicillium spp ., Aspergillus spp ., Microsporum spp. and Trichophyton mentagrophytes are also significant causes of infections in diabetic foot ulcers ( Musyoki, et al, 2022 ). Five cases of Aspergillus chronic subcutaneous infections in patients with diabetes were reported in a meta-analysis of 2,704 fungal isolates from human mycetoma ( van de Sande, 2013 ).…”
Section: Fungi In Chronic Woundsmentioning
confidence: 99%
“…2 Recently, a few studies have reported mycotic infections of the diabetic foot, mainly Candida species. 3 , 4 , 5 …”
Section: Introductionmentioning
confidence: 99%
“…Most of the diabetic foot infections are known to be caused by aerobic and anaerobic bacteria and in most cases polymicrobial 2 . Recently, a few studies have reported mycotic infections of the diabetic foot, mainly Candida species 3–5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation